2021
DOI: 10.3389/fonc.2021.716849
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Radiomics Signature: A Potential Biomarker for Prediction of Early and Late Recurrences of Hepatocellular Carcinoma After Resection

Abstract: ObjectivesTo explore the usefulness of spleen radiomics features based on contrast-enhanced computed tomography (CECT) in predicting early and late recurrences of hepatocellular carcinoma (HCC) patients after curative resection.MethodsThis retrospective study included 237 HCC patients who underwent CECT and curative resection between January 2006 to January 2016. Radiomic features were extracted from CECT images, and then the spleen radiomics signatures and the tumor radiomics signatures were built. Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Research in spleen radiomics is limited. Li et al 13 investigated the value of splenic radiomic features in predicting recurrence after radical resection of hepatocellular carcinoma and found that a hybrid model of microvascular invasion, tumor radiomic features, and splenic radiomic features for predicting early recurrence achieved the highest C‐index values of 0.780 (95% CI: 0.728–0.831) and 0.776 (95% CI: 0.716–0.836) for the training and validation groups, respectively. On analyzing late recurrence, splenic radiomic features were the only prognostic factors associated with the recurrence of advanced hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in spleen radiomics is limited. Li et al 13 investigated the value of splenic radiomic features in predicting recurrence after radical resection of hepatocellular carcinoma and found that a hybrid model of microvascular invasion, tumor radiomic features, and splenic radiomic features for predicting early recurrence achieved the highest C‐index values of 0.780 (95% CI: 0.728–0.831) and 0.776 (95% CI: 0.716–0.836) for the training and validation groups, respectively. On analyzing late recurrence, splenic radiomic features were the only prognostic factors associated with the recurrence of advanced hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 It is now extensively used to predict the survival prognosis and treatment efficacy of patients with EC. [9][10][11][12] Previous studies have reported that spleen radiomics predicts prognosis in patients with gastric cancer and recurrence in patients with hepatocellular carcinoma 13,14 ; however, none of them further explored its relationship with systemic immunity. We hypothesized that the spleen is a vital part of the immune system and, to some extent, reflects the systemic immunity of the organism.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the integration of features extracted from multiple organs proved advantageous. Li et al successfully improved the model’s performance in predicting early and late recurrence of hepatocellular carcinoma after resection by integrating splenic and liver features [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, for example, showed that splenic radiomics features on CT can predict the prognosis of gastric cancer patients [ 33 ]. Another study used the spleen’s radiomics signature on CT to predict the recurrence of HCC [ 34 ]. Additionally, considering lymphoma, Enke et al developed a radiomics model on CT to differentiate between spleen involvement versus controls, as well as to discriminate different subtypes of malignant lymphoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%